(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the importance of organizing a healthy lifestyle for primary school students, and it is also important to strengthen the physical and mental health of students, improve their immunity and prevent diseases in the future. It also shows the importance of teaching and supporting a healthy lifestyle for teachers and parents.